Edukasi dan Pendampingan Individu Penggunaan Alat Pendeteksi Nominal dan Keaslian Uang Berbasis Optik–UV bagi Penyandang Tunanetra - Eko Ari Wibowo; Widyastuti Widyastuti; Muhammad Nur Wahyu Hidayah; Wildan Afdalul Fadhi; Hamdi, Lazuardi Fatahilah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
People with visual impairment face barriers in cash transactions, particularly in identifying banknote denominations and verifying authenticity, which can reduce independence and increase vulnerability to fraud. This issue is also closely linked to the financial inclusion agenda, as access to reliable information on the value and authenticity of cash is a prerequisite for safe transactions among vulnerable groups. This community service program aimed to improve users’ competence through individualized, home-visit–based education and mentoring on an optical–UV sensor–based banknote denomination and authenticity detector with audio feedback. The program was implemented in collaboration with the Kebumen branches of PERTUNI and ITMI from October to December 2025. The intervention stages included an initial needs assessment, structured training using a concise module, hands-on practice through transaction scenarios, and follow-up mentoring. Evaluation employed a pre–post knowledge test, a practical performance checklist, and a usability questionnaire. Results indicated that the mean knowledge score increased from 55.1 to 80.7, and the success rate of denomination identification improved from 60.7% to 90.0%. This approach is relevant as an individualized mentoring model for blind communities when group-based training is difficult to implement.